A spy in exile : a thriller - De Shalit, Jonathan (Emily Bestler Books, Atria, 2019)
"In the upper echelons of Israel's intelligence community, an elite, secret unit discovers how easily the hunter can become the hunted. After Ya'ara Stein is forced out of her job at the Mossad--Israel's secret intelligence service--she is called upon by the prime minister for a classified job. The astute and deadly Stein is tasked with forming a secret unit that is answerable only to the prime minister. Made up of brilliant young recruits, Ya'ara's team faces a lethal terrorist cell with ties to old European factions. But the ghosts of the past are not the only threats they face, and the agents scramble to distinguish between fact and fiction as their enemies turn the tables and close in."--cProvided by publisher.